Sorafenib induced Hand Foot Skin Rash in FLT3 ITD mutated Acute Myeloid leukemia- A case report and review of literature - Jayastu Senapati; Anup J Devasia; Abhijeet Ganapule; Leni George; Auro Viswabandya (Mediterranean Journal of Hematology and Infectious Diseases)
Sorafenib is a novel small molecule multiple kinase inhibitor which has been used for metastatic renal cancer, hepatocellular cancer. Sorafenib induced skin rash has been discussed as a side effect in trials in both FLT3 wild type and mutated acute myeloid leukemia (AML) as monotherapy or as combination with other chemotherapeutic agents . We describe a patient with FLT 3 ITD mutated AML who was started on adjunctive Sorafenib therapy. Skin reactions manifested as NCI Grade III palmoplantar erythrodysesthesia (PPE), requiring drug discontinuation. Several pathogenic mechanisms have been implicated in Sorafenib induced skin reactions, but none has been conclusively proven. While treatment options are varied for early stage skin reactions, drug discontinuation remains the only possible therapy presently for severe grade skin reaction.